A atual crise econômica do distrito de Taunay: análise histórica e geográfica - Lucélia Souza Santiago (2021)
The District of Taunay, belongs to the municipality of Aquidauana/MS and is located approximately sixty kilometers from the seat of the municipality, which can be accessed by the BR-262 highway, to the West. The objective of this research is to make a Geographic and Historical analysis of the railroad and its economic activities, always comparing the before (development) and after (economic crisis) that reached the district with constant migrations in search of work, using as theoretical and methodological contribution authors who discuss the presence of the railway in the state of Mato Grosso do Sul, with emphasis on its importance. It was observed that around 1910, the railroad tracks started a development process for a long period not only in the district, but also throughout the state where the tracks passed and the train traveled. Taunay, at that time, was sparsely populated and had little economic development. As time went by, this population increased, just as in all places where the tracks passed, there was a railway village. The district's economy was not just the railroad that moved with its street vendors and the people who worked on it. Economic activities were also handled by limestone companies, street vendors, rural workers, businesses and large farms, based on livestock, public and private jobs. The current aspects are in the process of data collection, considering the current major events, pandemic crisis, which has hit the whole world. Currently, the old railway in the district is being remodeled and will start serving social assistance services to the population. Key-words: History of the District; Development Phases; Current Economic Portrait